Kulturang karera communicating Philippine horseracing culture - Ortuoste, Jennifer Rebecca Lacson (2016)
"Over the nearly 150 years of its existence, Philippine horseracing - karera - has developed its own signs, symbols and language as part of a culture by which its members conduct the activities that sustain it. This study explores the ways by which meanings are formed and spread in the horseracing subculture using an autoethnographical approach that maximizes the researcher's trove of personal knowledge, guided by a cultural studies perspective. After examining material artifacts, conducting in-depth interviews, and plumbing the researcher's lived experiences and observations in racing of over twenty years, it is clear that the people in horseracing created their community to fulfill objectives related to commerce, thereby creating a culture that maintains social order, constructing and spreading their ideas and meanings through communication. They construct and reach a consensus on meanings, which are then disseminated and learned in an interactive, immersive and contextualized experience. By these means racing creates and spreads its culture and maintain its social reality to meet human needs for livelihood and entertainment, a process that might find parallels in other Philippine subcultures."